Sleep duration and its links to psychological distress, health status, physical activity and body mass index among a large representative general population sample - Liang, Wenbin; Chikritzhs, Tanya (Scientific Research Publishing, 2013)
This study aimed to investigate associations between: (a) psychological distress, self-perceived health status and sleep duration among a large representative general population sample; and (b) patterns of sleep duration, physical activity and Body Mass Index among a subgroup of participants who self-reported as being in good health with low psychological distress. Data collected from six waves of the Nation Health Interview Surveys (NHISs) was employed. The results indicated that both psychological distress and self-perceived health status were strong predictors of sleep duration. Participants with high serious psychological distress scores reported sleeping 7 - 8 hours less often than those in low or moderate psychological distress and were also most likely to sleep for less than 6 hours or 9 or more hours. Similar patterns were observed for sleep duration by self-reported health status. Subgroup analysis including only participants in self-reported excellent or very good physical health with low mental distress scores showed that participants who engaged in higher frequencies of vigorous and strengthening exercises were more likely to sleep less than six hours, and participants with a BMI of 25 or higher were also more likely to sleep less than six hours.